Peran Pekerja Sosial Pada Proses Diversi Anak Berhadapan Dengan Hukum: Studi Kasus Unit Pelaksana Teknis Daerah Panti Sosial Anak Jroh Naguna Dinas Sosial Aceh) - Khairun, Afina Afiyati; Srimulyani, Eka; Amalia, Wirda (JAROW: Journal of Ar-Raniry on Social Work, 2025)
The increasing number of cases of Children in Conflict with the Law (ABH) in data obtained from the UPTD Jroh Naguna Children's Social Institution shows the need for synergy between various parties, including the government, law enforcement agencies, social workers, educational institutions, and the community. According to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, diversion is an effort to resolve children's cases outside the judicial process. The purpose of this study was to determine the role of social workers in the ABH diversion process and the stages of implementing diversion in ABH. This study used qualitative and descriptive methodologies. Data were obtained through observation, interviews, and documentation. The results of the study showed that social workers have a significant role in carrying out the diversion process for ABH. Social workers act as Enablers, Mediators, Motivators, and Educators. In addition, social workers also play a role in accompanying during the investigation process until the diversion deliberation process is carried out. Furthermore, the stages in implementing ABH diversion are the pre-diversion stage, the diversion implementation stage and the post-diversion stage. However, social workers face obstacles in carrying out their roles, such as difficulty communicating with ABH parents because they are very closed.